Crystal lattice engineering the novel substrates for III-nitride-oxide heterostructures - Osinsky, V.; Dyachenko, O. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2010)
In this work, we firstly investigated controlling the lattice parameter of IIIoxides
used as substrates for III-nitrides heterostructures. It was shown that the atomic
content change in III-sublattice gives large possibilities for precise cation controlling the
lattice parameters. The developed technique is promising to make ideal substrates in IIInitride
epitaxy of LED, LD and transistors with a high quantum efficiency and small
noise. This technology can be realized using MBE, MOSVD or CVD chloride-hydride
epitaxy with computer driving.